2017
DOI: 10.1159/000455981
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21 Regulates TNF-α-Induced CD40 Expression via the SIRT1-NF-κB Pathway in Renal Inner Medullary Collecting Duct Cells

Abstract: Background/Aims: Recent studies have indicated that microRNA-21 (miR-21) is involved in the inflammatory response in relation to renal disease. Sirtuin1 (SIRT1) exerts renoprotective properties by counteracting inflammation. The activation of CD40 triggers inflammation that participates in renal inflammation and injury. The relationship between miR-21, SIRT1 and CD40, however, remains elusive. Methods: Immunohistochemistry, small-interfering RNA (siRNA) transfection, quantitative real-time PCR and western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…Moreover, miR-21-5p might protect monocyte from IHR-induced cell apoptosis and cytotoxicity by inhibiting TLR4/TNF-α/IL-6R-mediated inflammation. In line with our findings, previous studies have shown that miR-21 has anti-inflammatory and anti-apoptosis effects by inhibiting NF-κB-TNF-α-TLR and PDCD4-caspase-3 pathways, respectively, while TNF-α can suppress miR-21 functional axis [16][17][18]20,25,29,36]. The results open the possibility of using miR-21-5p mimic to overcome systemic inflammation and improve outcomes in OSA patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, miR-21-5p might protect monocyte from IHR-induced cell apoptosis and cytotoxicity by inhibiting TLR4/TNF-α/IL-6R-mediated inflammation. In line with our findings, previous studies have shown that miR-21 has anti-inflammatory and anti-apoptosis effects by inhibiting NF-κB-TNF-α-TLR and PDCD4-caspase-3 pathways, respectively, while TNF-α can suppress miR-21 functional axis [16][17][18]20,25,29,36]. The results open the possibility of using miR-21-5p mimic to overcome systemic inflammation and improve outcomes in OSA patients.…”
Section: Discussionsupporting
confidence: 91%
“…Certain miRNAs, including miR-21 and miR-23a, are induced by TLR signaling or negatively regulate TLR signaling [14]. Specifically, miR-21 is involved in anti-inflammatory response via inhibiting TLR, NF-κB, IL-6, and TNF-α signaling pathway, while high concentrations of TNF-α inhibit miR-21 functional axis [15][16][17][18][19][20]. In contrast, miR-23a may be involved in pro-inflammatory response via enhancing TNF-α and IL-6 secretions, while TLR signaling can inhibit miR-23a expression [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Recent results have indicated that nuclear factor (NF)-κB signaling has a major role in innate immunity defense whereas sirtulin (SIRT)1 regulates the oxidative respiration and cellular survival ( 9 ). Additionally, NF-κB p65 signaling may stimulate glycolytic energy flux during acute inflammation, whereas SIRT1 activation inhibits NF-κB p65 signaling and enhances oxidative metabolism and reduces the expression of inflammatory and fibrotic factors, including tumor necrosis factor-α and transforming growth factor-β) ( 10 ). Previous findings have indicated that SIRT1 inhibits NF-κB p65 signaling directly by deacetylating the p65 subunit of NF-κB complex ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The proteins associated with cell apoptosis were detected by apoptosis antibody array, and quantitative analysis revealed that TAP1 and NF-κB-mediated apoptosis signaling pathway was the most important pathway involved in PdT, with hematoporphyrin-induced apoptosis observed in glioma U87 cells. A recent study reported that miR-21 significantly contributes to the inflammatory response via the sirtuin 1-NF-κB signaling pathway (36). It implied that the miRNAs that specifically targeted TAP1 and NF-κB are important therapeutic targets (Fig.…”
Section: Discussionmentioning
confidence: 99%